Changes in Biochemical Parameters in Acute Pyelonephritis in Different Trimesters of Pregnancy Before and After Treatment - Kholimenko, I.M.; Konoplja, A.A.; Bushmina, O.N.; Konoplja, E.N.; Kravcov, A.Ju. (Biomedical Chemistry: Research and Methods, 2025)
Gestational pyelonephritis is characterized by an annual increase in morbidity and complications, which negatively affect the course of pregnancy and childbirth in 3-17% of women in Russia. The discrepancy within the normally balanced oxidant-antioxidant system underlies the pathogenesis of many diseases of pregnant women, with a significant role atributed to oxidative stress and systemic inflammatory response. Biochemical laboratory parameters of systemic inflammation, oxidant-antioxidant system and endothelial dysfunction in peripheral blood plasma and urine were studied.The study included 115 women (mean age 25.1±4.3 years), divided into groups: comparison - 20 healthy women, 20 nonpregnant patients with a verified diagnosis of acute serous pyelonephritis; main groups of 15 women each: three groups with acute pyelonephritis in the 1st, 2nd and 3rd trimesters of pregnancy before and after basic therapy and two groups with acute pyelonephritis in the 2nd and 3rd trimesters of gestation with the inclusion of Viferon in the basic treatment. At all periods of gestation in conditions of acute pyelonephritis, to a greater extent in the 2nd and 3rd trimesters, the development of systemic inflammation, oxidative stress and endothelial dysfunction was established, as evidenced by an increase in the content of stable metabolites of nitric oxide, acyl hydroperoxides, malonic dialdehyde, markers of systemic inflammatory response (C-reactive protein and neopterin) in the plasma of peripheral blood and urine, a decrease in antioxidant defense factors and the level of endothelin-1. Incomplete relief of metabolic disorders by basic therapy was revealed, especially in the late stages of gestation. The inclusion of Viferon in traditional therapy of acute pyelonephritis in the 2nd and 3rd trimesters was more effective of pregnancy.